Bishkek Protocol. How It Was: Memories and Comments - Andrey V. Toropygin (Евразийская интеграция: экономика, право, политика)
This year marks the twenty-five years since the signing of the Bishkek Protocol (1994), which played a significant role in resolving the conﬂict over Nagorno-Karabakh and became a significant contribution of the Interparliamentary Assembly of the Commonwealth of Independent States in peacekeeping activities during the post-soviet period. The article is dedicated to this event. The author in 1994 was an Assistant Deputy Secretary General of the IPA CIS Council — Representative of the Federal Assembly of the Russian Federation in the IPA CIS, recalls the atmosphere of those days and the negotiations related to the preparation and signing of the document. The events connected with the preparation of signing certainly allow us to look at some aspects of the development of parliamentary diplomacy, which is important, both for the development of diplomacy and parliamentarism in general.